A comparative between the supply and energy needs of hospitalized patients under enteral nutritional therapy - Taborda, Aline Gamarra; Pizzato, Alessandra Campani (Clinical and Biomedical Research, 2017)
Introduction: Patients who are at risk of malnutrition are potential candidates for the use of enteral nutritional therapy (ENT), since it allows a more effective control of the patient’s nutrition. When oral food intake is impossible or insufficient, enteral nutrition is the most appropriate physiological option aiming at the maintenance of gastrointestinal trophism. Studies show us that the protein-caloric needs of the hospitalized patients are seldom reached in the feeding tube supply, staying routinely between 70% and 80% of their needs. Methods: A descriptive study was conducted based on secondary data collected by the Multidisciplinary Team of Nutritional Therapy of a university hospital in Brazil to compare the caloric intake received by the hospitalized patients when in enteral nutritional therapy with their real needs. Results: A total of 43 adult inpatients who were in exclusive enteral nutrition were assessed. It was observed that the mean caloric intake received by the patients was 1,767±271kcal/day, reaching 94% of the estimated caloric needs, which were 321kcal/day. In relation to the nutritional status of the analyzed patients, it was found that 38% were at nutritional risk. Conclusion: The creation of protocols of nutritional support is of great importance to guide professionals in the prescription of ENT, aiming to improve the nutritional intake offered to hospitalized patients. Keywords: Enteral nutrition; malnutrition; caloric intake; caloric needs